Modulated Start-Up Mode of Cancer Cell Migration Through Spinophilin-Tubular Networks - Hwang, Soyoung; Lee, Peter Chang-Whan; Shin, Dong Min; Hong, Jeong Hee (Frontiers in Cell and Developmental Biology, 2021)
Spinophilin (SPL) is a multifunctional actin-binding scaffolding protein. Although increased research on SPL in cancer biology has revealed a tumor suppressive role, its modulation in cancer biology, and oncological relevance remains elusive. Thus, we determined the role of SPL in the modulation of the junctional network and cellular migration in A549 lung cancer cell line. Knockdown of SPL promoted cancer cell invasion in agarose spot and scratch wound assays. Attenuation of SPL expression also enhanced invadopodia, as revealed by enhanced vinculin spots, and enhanced sodium bicarbonate cotransporter NBC activity without enhancing membranous expression of NBCn1. Disruption of the tubular structure with nocodazole treatment revealed enhanced SPL expression and reduced NBC activity and A549 migration. SPL-mediated junctional modulation and tubular stability affected bicarbonate transporter activity in A549 cells. The junctional modulatory function of SPL in start-up migration, such as remodeling of tight junctions, enhanced invadopodia, and increased NBC activity, revealed here would support fundamental research and the development of an initial target against lung cancer cell migration.